2018
DOI: 10.1155/2018/6202876
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bimodal Imaging Agent Targeting HER2 Molecule of Breast Cancer

Abstract: Nanobubble (NB), a newly developed nanoscaled ultrasound contrast agent (UCA) for molecular imaging, has been widely researched for these years. Targeting it with functional molecule, nanobubble can adhere selectively to cellular epitopes and receptors outside the vasculature via enhanced permeability and retention (EPR) effect of tumor blood vessel. To enhance the targeting rate of our previous prepared NBs-Affibody for HER2 (+) breast cancer imaging, we introduced a near-infrared fluorescent (NIRF) dye, IR78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Nanobubbles have been widely used in ultrasound molecular imaging and drug/gene targeting delivery. When conjugated with specific ligands, nanobubbles can be used as a probe in ultrasound molecular imaging of various diseases, such as tumor (Lv et al, 2018), allograft rejection (Liu et al, 2018), and so on. Compared with microbubbles, nanobubbles can migrate from vasculature to the extravascular target site, which greatly expanded the application range of ultrasound molecular imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Nanobubbles have been widely used in ultrasound molecular imaging and drug/gene targeting delivery. When conjugated with specific ligands, nanobubbles can be used as a probe in ultrasound molecular imaging of various diseases, such as tumor (Lv et al, 2018), allograft rejection (Liu et al, 2018), and so on. Compared with microbubbles, nanobubbles can migrate from vasculature to the extravascular target site, which greatly expanded the application range of ultrasound molecular imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo experiments demonstrated that the obtained Y1Rmediated fluorescent nanobubbles had good ultrasound contrast enhancement and targeting ability to Y1 receptors-overexpressing breast cancer. Near-infrared (NIR) heptamethine cyanine dyes with fluorescence property and tumor-targeting characteristic, such as IR-780 [42,43] and IR-783 [44], are loaded into the shell of nanobubbles for tumor-specific ultrasound/ fluorescence dual-modal imaging. For example, Shen et al synthetized a novel targeted bimodal nanobubbles, FA-NBs-IR780, with a uniform nano-size (591 ± 52 nm) [43].…”
Section: Micro/nanobubbles Mediated Multimodal Imagingmentioning
confidence: 99%
“…NB can extravasate through the vascular wall into the extravascular space [22] and can easily accumulate in the tumour due to the EPR effect. Moreover, NB was established connections with HER2 a body and a near-infra uorescent dye IR783 to enable the formation of nanobubble-IR783-a body [23,24] which markedly targets HER2-positive breast cancer and could be applied in targeting drug delivery system.…”
Section: Introductionmentioning
confidence: 99%